The formation of seed productivity of a peas collection of different morphotypes in the Middle Volga region (PoVolzhie) - A. I. Katyuk (Зерновое хозяйство России)
The purpose of the current paper was to study the features of the formation of productivity components and their correlation in the peas varieties of different morphotypes to develop new breeding material with high productivity. The study was carried out in the conditions of the Middle Volga region (PoVolzhie) in 2005, 2008-2011 and 2018-2019 according to generally accepted methods. The objects of the study were the pea varieties of various ecological and geographical origin of domestic and foreign selection. There were studied from 50 to 194 varieties in different years. High seed productivity was identified in the mustachioed determinant group (3.5 g) and the chameleon group (4.0 g). The seed weight in the peas varieties belonging to these groups was 0.5 and 1.0 g per plant or on 16-30% higher than that of the traditional leafy indeterminate group of varieties, respectively. There has been established a positive correlation between seed weight per plant and number of seeds per plant (r = 0.742-0.887), number of beans per plant (r = 0.736-0.814) and seed weight per fertile node (r = 0.716-0.851). There has been shown that the variability of pea productivity was largely stipulated by number of seeds per plant in the favorable climatic years and by seed weight per fertile node in the arid years. In various morphological groups there have been identified the sources of high seed productivity, maximally adapted to the conditions of the region. The best sources ‘Ras tip', ‘Az26', ‘Az96637', ‘Flagman 9', ‘Az931776', the determinant ‘VSKhI', ‘Harvus', ‘Faraon', ‘Flagman 7', ‘Orel', ‘Kuibyshevsky', ‘Voronezhsky', ‘B3390/11') will be included in the breeding process.